Biological Activity of New Cyclophosphazene Derivatives Including Fluorenylidene‐Bridged Cyclophosphazenes. Issue 34 (13th September 2018) - Yıldırım, Tuba; Şenkuytu, Elif; Ergene, Emel; Bilgin, Kemal; Uludağ, Yıldız; Çiftçi, Gönül Yenilmez
Abstract: In this study, new cyclophosphazene compounds were synthesized characterized and their biological activity studies were performed. The structural investigations of the compounds were verified by elemental analyses, mass spectrometry, 1 H, 31 P NMR techniques. Later, the effects of the synthesized compounds to DNA were screened using DNA interaction analysis and cleavage methods by utilizing pUC18 plasmid. The results showed that the compounds14, 40 and45 caused Form III (linearized DNA) plasmid DNA, indicating the interaction of these compounds with the plasmid DNA. Abstract : In this study, new cyclophosphazene compounds were synthesized and characterized. The biological activity studies of the newly and previously synthesized compounds were carried out. The antimicrobial susceptibility tests showed that the synthesized cyclophosphazene compounds have antibacterial activity. The effects of the synthesized compounds to DNA were screened using DNA interaction analysis. Some compounds have shown DNA binding properties.